Cultural Issues That Affect Computer Programming: A Study of Vietnamese in Higher Education - Ashok Kumar Veerasamy; Mikko-Jussi Laakso (Mohammad Arif Siddiqui, 2022)
Every society has its own cultural system which ultimately permeates and influences their educational system. Cultural attitudes impact the way students learn and participate in education. A few social practices or culture values may affect student engagement, learning process and learning experience in computer programming education. The purpose of this research was to investigate the impact of students’ cultural attitudes on learning programming courses in Vietnam. To identify this, a questionnaire was designed and distributed to Vietnamese undergraduate IT students in order to measure the relationship between cultural attitudes and student engagement in learning. This study used Geert Hofstede’s defined cultural dimensions of power distance, and collectivism versus individualism as combined factors that affect student participation and engagement. The survey results were analyzed by the correlation coefficient statistical method to examine the statistical relationships that exist between student’s power dependency culture and participation in learning. The survey results confirmed that many students completed their secondary education in a teacher centered environment and students are hesitant to express their opinions to teachers, and prefer to use existing solutions to complete their work. Moreover, statistical results partially supported the conclusion that, student’s high power distance culture may affect their engagement in learning programming courses though many students are interested in active learning environments.